TEACHING PUBLIC ADMINISTRATION WITH POP CULTURE - Borry, Erin L.; Jones, Peter A. ([S.l.] : ROUTLEDGE, 2025)
This book offers faculty teaching in public administration and public affairs programs a playbook for using popular culture as a pedagogical tool in the classroom. Authors Erin L. Borry and Peter A. Jones build a pedagogical framework, detailing the richness and range of media through which pop culture can be accessed, and demonstrate how best to integrate different forms of pop culture to achieve various learning goals. The breadth of content available and practical applicability to the public administration degree offer many opportunities to incorporate pop culture into the curriculum, including introductory courses in public administration and public service, as well as more advanced budgeting, statistics, ethics, social equity, and open government courses, to name a few. This book offers some examples of pop culture that instructors can readily adapt for use in their own courses, as well as sample assignments and various types of group work, including simulations. Teaching Public Administration with Pop Culture will be of enormous benefit to instructors of public affairs undergraduate and graduate students, as well as to those teaching in the areas of political science, civics, social studies, and government in higher and K12 education settings.
Keywords: Public administration -- Study and teaching; POLITICAL SCIENCE / Public Affairs & Administration; EDUCATION / Higher